Advancing Humanity: Sharīʻah-Compliant Innovations in Contemporary Technology (Al-Qamar, 2025)
The ethical need for the development of science and technology to prioritise human benefit is analyzed in this paper. With a focus on Shari'ah's five basic aims namely preserving faith, life, intellect, lineage and property, the ethical consequences of scientific progress are explored through the prism of Islamic law. If ethical considerations are not incorporated in the field of science and technology, we will observe further chaos in the society. This paper concludes the fact that the human beings will get maximum benefits and the impending damages to the society will be minimized if adherence to the five main aims of Shari’ah is made.
Keywords: aqasidal-Shari’ah,Islam; Islam; Science; Technology; ethics